Roles and functions of stakeholders in implementing energy retrofits in the hotel sector. Issue 5 (26th May 2020) - Fasna, M.F.F.; Gunatilake, Sachie
Abstract : Purpose: The success of energy retrofits (ER) projects is highly dependent on the involvement of right stakeholders at the right stage. So far, little insight is available from previous literature on the involvement of different stakeholders during various stages of the ER decision-making process, and their roles and functions in the respective stages. This is specifically true in the context of Energy Service Company (ESCO) led ER projects, which is an emerging trend in the current context. Hence, this paper aims to investigate the roles and functions of stakeholders during different stages of an ESCO-led ER project in the hotel sector. Design/methodology/approach: An in-depth case study was conducted in a selected hotel building to gain insights into the roles and functions of stakeholders throughout the project stages. To collect the required data, face-to-face semi-structured interviews were conducted with seven selected respondents within the case. Findings: The study identified nine key stakeholders that were involved during five different project stages along with their functions. Based on these identified functions, four main roles (i.e. decision-maker, performer, monitor/observer, and supporter) emerged that were reflective of the nature of the stakeholders' involvement in different stages of the decision-making process. Owner/client, facilities manager (FM), ESCO and architect attached to ESCO emerged as the key "decision-makers" during project implementation process. Originality/value: The outcomes of this research would be useful in ensuring the proactive involvement of all the identified stakeholders in respective project stages of ESCO led ER projects in the hotel sector.